2015
DOI: 10.4314/jab.v89i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Évaluation in vitro de l’activité antiplasmodiale d’extraits de plantes issues de la pharmacopée traditionnelle du Niger

Abstract: RÉSUMÉProblématique : Le paludisme demeure un problème majeur de santé publique dans les pays intertropicaux. La situation socio-économique des pays d'endémie palustre couplée au développement de la résistance des souches de Plasmodium falciparum aux molécules couramment utilisées exigent la mise au point de nouveaux médicaments antipaludiques. Objectif : L'activité antiplasmodiale d'extraits éthanoliques dégraissés de six plantes issues de la pharmacopée traditionnelle du Niger a été évaluée et comparée à cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
1
6
0
2
Order By: Relevance
“…30,31 In addition, the promising effect of these four extracts could be due to the cumulative presence of compounds such as polyphenols, triterpenes, and alkaloids in the extracts which could have a synergistic effect on P. falciparum. 32,33 By comparing the IC 50 of the hydroethanolic extract BioImpacts, 2020, 10(3), 151-157 156 from A. djalonensis obtained in this study with those reported in the literature, it was found that these results are close to those reported by Attemene et al 28 Indeed, these authors obtained an IC 50 of 15.94 µg/mL on strain K1 for the hydroethanolic extract from the same plant. In 2007, work by Muthaura et al showed that the aqueous extract from H. madagascariensis contained active ingredients on the chloroquine-resistant K1 strain of P. falciparum with an IC 50 of 3.1 µg/mL.…”
Section: Discussionsupporting
confidence: 82%
“…30,31 In addition, the promising effect of these four extracts could be due to the cumulative presence of compounds such as polyphenols, triterpenes, and alkaloids in the extracts which could have a synergistic effect on P. falciparum. 32,33 By comparing the IC 50 of the hydroethanolic extract BioImpacts, 2020, 10(3), 151-157 156 from A. djalonensis obtained in this study with those reported in the literature, it was found that these results are close to those reported by Attemene et al 28 Indeed, these authors obtained an IC 50 of 15.94 µg/mL on strain K1 for the hydroethanolic extract from the same plant. In 2007, work by Muthaura et al showed that the aqueous extract from H. madagascariensis contained active ingredients on the chloroquine-resistant K1 strain of P. falciparum with an IC 50 of 3.1 µg/mL.…”
Section: Discussionsupporting
confidence: 82%
“…L'activité antiplasmodiale observée au niveau du Senna occidentalis justifie effectivement l'utilisation traditionnelle de cette espèce dans le traitement du paludisme. Les extraits : éthanolique, éther de pétrole de la feuille de Senna occidentalis ont donné respectivement des CI50 de 5,3µg/mL et 1,4µg/mL (Tona et al, 2004) ; pour le même extrait éthanolique des feuilles, Zirihi et al, (2005) et Nassirou et al, (2015) ont obtenu respectivement des CI50 de 36, ± 5,6 µg/mL et 10,4 µg/mL puis Ménan et al, (2006) ont trouvé que l'extrait aqueux n'est pas actif comparativement à l'extrait éthanolique et pentanolique. Ces résultats sont semblables à ceux obtenus par nos travaux.…”
Section: Discussionunclassified
“…Some studies argue that major phytochemical groups such as flavonoids, tannins, saponins, coumarins, alkaloids, triterpenes, sesquiterpenes and steroids [ 47 , 48 , 49 ] may be responsible for the anti-malarial activity observed in some plants. As an example, L. camara aqueous and ethanolic leaf extracts have shown antimalarial activity close to that of the standard drug chloroquine.…”
Section: Resultsmentioning
confidence: 99%
“…L. camara leaves, a plant of the same genus, has been shown to have an IC 50 value similar to that found in this study [45,46], highlighting the interest of this plant genus for the treatment of malaria and encouraging further studies. Some studies argue that major phytochemical groups such as flavonoids, tannins, saponins, coumarins, alkaloids, triterpenes, sesquiterpenes and steroids [47][48][49] may be responsible for the anti-malarial activity observed in some plants. As an example, L. camara aqueous and ethanolic leaf extracts have shown antimalarial activity close to that of the standard drug chloroquine.…”
Section: Anti-malarial Activitymentioning
confidence: 99%